2010
DOI: 10.1590/s0104-56872010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Manifestações eletrofisiológicas em adultos com HIV/AIDS submetidos e não-submetidos à terapia anti-retroviral

Abstract: TEMA: os potenciais evocados auditivos (PEA) avaliam a atividade neuroelétrica na via auditiva, desde o nervo auditivo até o córtex cerebral, em resposta a um estímulo ou evento acústico. Estudos demonstram anormalidades eletrofisiológicas em indivíduos com HIV/AIDS. OBJETIVO: caracterizar as manifestações eletrofisiológicas da audição em adultos com HIV/AIDS, comparando os resultados obtidos no grupo exposto a tratamento anti-retroviral com os obtidos no grupo não exposto a tratamento. MÉTODO: realizada avali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
1
17
1
1
Order By: Relevance
“…The obtained results confirmed one study in which the author, to characterize the results of audiologic assessment in children and adults with HIV/AIDS, observed higher occurrence of conductive hearing loss in children (92.9% of the cases), whereas in the adult population there was higher occurrence of sensorineural hearing loss (44.4% of the cases) (26) . Upon comparing the subjects with HIV/AIDS submitted and not submitted to antiretroviral therapy, the data observed in the present study showed that there were no differences in occurrence of hearing loss in these two groups, confirming the results of some specific studies in the area (14,19,20) , and disagreeing with other studies that correlated the use of antiretroviral medication with higher occurrence of hearing impairment (5,9,(15)(16)(17)(18)21) . Considering the data found in the present study, we could observe that sensorineural hearing loss was associated with the presence of HIV virus and its adverse effects in the infected subject, in agreement with other studies published in the literature (10)(11)(12)14,24,25) .…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…The obtained results confirmed one study in which the author, to characterize the results of audiologic assessment in children and adults with HIV/AIDS, observed higher occurrence of conductive hearing loss in children (92.9% of the cases), whereas in the adult population there was higher occurrence of sensorineural hearing loss (44.4% of the cases) (26) . Upon comparing the subjects with HIV/AIDS submitted and not submitted to antiretroviral therapy, the data observed in the present study showed that there were no differences in occurrence of hearing loss in these two groups, confirming the results of some specific studies in the area (14,19,20) , and disagreeing with other studies that correlated the use of antiretroviral medication with higher occurrence of hearing impairment (5,9,(15)(16)(17)(18)21) . Considering the data found in the present study, we could observe that sensorineural hearing loss was associated with the presence of HIV virus and its adverse effects in the infected subject, in agreement with other studies published in the literature (10)(11)(12)14,24,25) .…”
Section: Discussioncontrasting
confidence: 63%
“…It is important to emphasize that the existing abnormalities may occur due to the action of the virus upon the body, the immunosuppression and presence of opportunistic infections, as well as the action of antiretroviral medication and potentially ototoxic medication (5,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)24) . The specialized literature has shown widely diversified results concerning the occurrence of hearing loss in the population with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Porém, alterações na via auditiva central podem levar a comprometimentos de caráter lesional (efeito eletrodo), ou funcional (efeito orelha), que, por muitas vezes, não são identificados na avaliação audiológica convencional (Matas et al, 2010).…”
Section: Discussionunclassified